Mammadova, Fidan - (:unkn) unknown (My University, 2026)
Fidan Aliagha Mammadova received her Bachelor's degree in Engineering Economics and Management from the Azerbaijan University of Architecture and Construction (2001–2005) and her Master's degree in Economics and Management of Production and Service Sectors from the same university in 2009. From 2010 to 2012, she worked as a Junior Research Assistant at Project Institute LLC, affiliated with the Azerbaijan University of Architecture and Construction. In 2017, she was awarded the degree of Doctor of Philosophy (PhD) in Economics (FD No. 10331). In 2023, she was awarded the academic title of Associate Professor in Economics (specialty 5312.01). Since 2016, Dr. Mammadova has been working at the Department of Business Economics and Management of the Azerbaijan University of Architecture and Construction. From 2016 to 2023, she served as a PhD Lecturer and has held the position of Associate Professor since 2023. She is the author of 123 scientific publications, 46 curricula, one methodological manual, and three textbooks.